2020
DOI: 10.5582/ddt.2020.03107
|View full text |Cite
|
Sign up to set email alerts
|

Finger sweating levels evaluated by video capillaroscopy system are increased in patients with systemic sclerosis compared to pre-clinical stage patients

Abstract: New strategies for early diagnosis and careful follow-up of systemic sclerosis are urgently needed. We unconventionally used a video capillaroscopy system to measure the amount of sweating on finger pads, and investigated its clinical significance. Thirty-three Japanese patients who were diagnosed with typical or pre-clinical stage patients of systemic sclerosis were included in this study. Five healthy subjects were also included. Among twenty-one patients with typical systemic sclerosis that fulfilled ACR/EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In addition, for early detection, low serum concentration of carbonic anhydrase 9 (CA9) and microRNA-29 in pre-clinical stage SSc may be utilized as early diagnostic markers (1,2). Also, we found increased sweating levels on finger pads in SSc patients, and demonstrated its clinical significance for early diagnosis of SSc (3).…”
Section: Introductionmentioning
confidence: 69%
“…In addition, for early detection, low serum concentration of carbonic anhydrase 9 (CA9) and microRNA-29 in pre-clinical stage SSc may be utilized as early diagnostic markers (1,2). Also, we found increased sweating levels on finger pads in SSc patients, and demonstrated its clinical significance for early diagnosis of SSc (3).…”
Section: Introductionmentioning
confidence: 69%
“…Increased winter sweating with severe pain in Raynaud's phenomenon might explain the phenomenon of increased winter sweating in some SCTD patients shown in Figure 1. Tabata et al studied sweating in SSc patients by using capillaroscopy and reported that 7 out of 21 patients developed increased sweating, although they did not perform a seasonal analysis 42 . The mechanism by which the overactivity of the sympathetic nerves that causes Raynaud's phenomenon affects sweating remains to be explored in additional studies involving a larger patient cohort, autonomic function tests, and pathological examination.…”
Section: Discussionmentioning
confidence: 99%